2013
DOI: 10.3997/1873-0604.2013042
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of the relationship between NMR relaxation and permeability in sands and gravels

Abstract: The accuracy of NMR-derived permeability estimates in sands and gravels are examined through simulations on numerical grain packs composed of uniform spherical grains. The packs consisted of randomly packed grains, with grain sizes set to represent a range corresponding to sands and gravels. The material properties for each pack were quantified through numerical analysis and the NMR response was simulated for a range of surface relaxivity values. The agreement between the numerically-derived permeability estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In particular, this is the case for materials containing large pores (e.g., Dlugosch et al, 2013;Dlubac et al, 2014) that are of interest for this study. One major outcome of the work of Brownstein and Tarr (1979) is summarized in Figure 2.…”
Section: Nmr Relaxation Times Theorymentioning
confidence: 99%
“…In particular, this is the case for materials containing large pores (e.g., Dlugosch et al, 2013;Dlubac et al, 2014) that are of interest for this study. One major outcome of the work of Brownstein and Tarr (1979) is summarized in Figure 2.…”
Section: Nmr Relaxation Times Theorymentioning
confidence: 99%
“…In Table , we compare reported b values for the lithologic constant when m = 1, found to be the optimal result in this study, and for m = 4, the standard value for petroleum applications. The table includes the standard b values and reported range of values for consolidated sandstones for petroleum applications (Kenyon ; Straley et al ); the values reported for the High Plains aquifer (Dlubac ; Dlubac et al ); and the values found in this study. We observe that as the material type becomes more consolidated (from bottom to top of the table), b decreases by about an order of magnitude in going from unconsolidated to un/semi‐consolidated material and then another order of magnitude in going to consolidated material.…”
Section: Resultsmentioning
confidence: 92%
“…The relaxation time constant of the NMR signal, that is, the time it takes for the nuclear spins to reequilibrate to their initial state after being perturbed by an energizing pulse, contains information about the pore size distribution (Bird et al, ; Brownstein & Tarr, ; Hinedi et al, ; Müller‐Petke et al, ). Taken together, the NMR parameters have been linked to hydraulic conductivity ( K ) through the use of various empirical relationships (Daigle & Dugan, ; Daigle et al, ; Dlubac et al, , ; Dlugosch et al, ; Knight et al, ; Legchenko et al, ; Vilhelmsen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The relaxation time constant of the NMR signal, that is, the time it takes for the nuclear spins to reequilibrate to their initial state after being perturbed by an energizing pulse, contains information about the pore size distribution (Bird et al, 2005;Brownstein & Tarr, 1979;Hinedi et al, 1997;Müller-Petke et al, 2015). Taken together, the NMR parameters have been linked to hydraulic conductivity (K) through the use of various empirical relationships (Daigle & Dugan, 2009;Daigle et al, 2014;Dlubac et al, 2014Dlubac et al, , 2013Dlugosch et al, 2013;Knight et al, 2016;Legchenko et al, 2004;Vilhelmsen et al, 2014). NMR logging has been used for decades in the petroleum industry to estimate the hydraulic properties of reservoirs (Coates et al, 1999;Daigle & Dugan, 2009, 2011Dunn et al, 2002;Kleinberg & Jackson, 2001).…”
Section: Introductionmentioning
confidence: 99%